Peran Guru Agama Hindu dalam Penguatan Sradha dan Bhakti Siswa Sekolah Dasar pada Abad-21 Studi Kasus di Sekolah Dasar Negeri 2 Tlogotirto Kabupaten Sragen - Widi Dea Santi; Farida Setyaningsih; Putu Budiadnya (Samsara Institute Publisher, 2026)
Strengthening the devotion and devotion of elementary school students through a contextual learning approach and the habituation of religious practices to form a character of discipline, honesty, politeness, and independence in worship. This research is qualitative with a descriptive case study method, analyzed using the Miles and Huberman model. The theoretical basis includes role theory, religious theory, and humanistic theory. Primary data sources were obtained from Hindu Religion teachers, students, principals, and parents, while secondary data were from related literature. Data collection techniques included participant observation, in-depth interviews, documentation, and literature studies. Data analysis was carried out through the stages of data reduction, data display, and conclusion verification. The focus of the research is the role of Hindu Religion teachers in strengthening the devotion and devotion of students at Elementary School 2 Tlogotirto The main obstacles include the dominance of gadgets, variations in family backgrounds, and weak religious habits at home; added to the difficulty of teachers in digital adaptation and the lack of school-family synergy. The solution strategies implemented: 1) Learning Innovation: Utilization of storytelling, video media, educational games, and real practices (joint prayer, daily prayers, pasraman) that increase student motivation. 2) Role Modeling and a Humanistic Approach: Integrating the synergy of the Four Teachers for sustainable spiritual development. 3) Stakeholder Collaboration: Intensifying communication with parents to foster the inculcation of Hindu values ​​(dharma, satya, ahimsa) within the home environment. The implications of this strategy are manifested in improving students' religious character, discipline, and moral resilience.